The Influence and Adaptation of Observatories in Islamic Civilization: A Case of Malaysia - Safiai, Mohd Hafiz; Hasan, Salmah Abu; Dimyati, Mohd Saifullah; Azam, Ahmad Ibrahim; Jamsari, Ezad Azraai; De Graaf, Wilfred (Journal of Al-Tamaddun, 2024)
This article explores the historical development of observatories for astronomical pursuits within the context of Muslim civilization. It aims to provide an overview of how observatories evolved alongside advancements in astronomy during the Islamic caliphate. The study investigates the parallels between Malaysian astrofiqh observatories and those established during the Islamic civilization era, employing a qualitative approach involving instrument observation, interviews, and document analysis. The findings reveal that the ‘Abbasid caliphate led in establishing observatories for educational and research purposes in astronomy. Key factors contributing to the success of observatory development include the rulers’ support, intellectual dedication, and political stability. Furthermore, the study highlights specific similarities between Malaysian astrofiqh observatories and their historical counterparts, encompassing various aspects such as objectives, physical features, instruments, and nomenclature.